Advancing CO2++ Modeling in the Martian Dayside Ionosphere: Insights from Natural Lifetime Analysis - Long Cheng; Erik Vigren; Moa Persson; Hao Gu; Jun Cui (The Astrophysical Journal)
The molecular dication CO _2 ^++ has, as previously reported, been detected in the Martian ionosphere by the Neutral Gas and Ion Mass Spectrometer on the Mars Atmosphere and Volatile Evolution (MAVEN) mission. Photochemical models have also been developed to reproduce the CO _2 ^++ density in the Martian dayside ionosphere but underestimate significantly the observations. In this study, we examine the influence of the CO _2 ^++ natural lifetime against spontaneous dissociation on its modeled density. We show that extending the assumed CO _2 ^++ lifetime significantly reduces the discrepancy between the photochemical model predictions and MAVEN observations. Specifically, when treating CO _2 ^++ as stable against natural dissociation, instead of invoking a lifetime of 4 s as done in previous studies, the data-to-model ratio comes close to unity throughout the altitude range 160–220 km. We argue that stability of CO _2 ^++ against natural dissociation does not necessarily conflict with results from a frequently cited experimental investigation. Our study provides new insights for advancing photochemical modeling of the Martian ionosphere and underscores the need for further laboratory measurements targeting fundamental properties of doubly charged ions.